in silico Study Reveals Potential Docking Sites of δ 2-isoxazolines derivates for Inhibiting Russell’s Viper PLA2 Toxin - Kholilah, Tsaniyah Nur; Widodo, Nashi; Kurniawan, Nia (Journal of Tropical Life Science, 2021)
Snake venom phospholipase A2s (svPLA2s) has been known as the most abundant component and predominant cause of Russell’s viper envenomation. Limitation to serum therapy and considerable pharmacological interest led the researcher to synthesized multi-toxic PLA2 inhibitors, δ2-isoxazolines derivate. Although δ2- isoxazolines derivate already proved inhibitor activity in Group II svPLA2 with known IC50, their mechanism of action remains unveiled. Our recent study investigated their inhibitory activity via molecular docking. The virtual screening revealed that the ligand with diverse structures tied to the relatively same active site region. The result sheds light on the significance of His48 and Asp49 as part of the pro-inflammatory eliciting region. ADME analysis was also performed to filter and identify the best potential inhibitor acceptable for human use. This moiety leads to finding a better therapeutic strategy of svPLA2 inhibitors both as an alternative to serum anti-venom treatment.